Gender, Utopias and the Savage Slot: The Role of Anthropology in the (De)Construction of a Concept - Peano, Irene (ETHICS IN PROGRESS, 2019)
The paper addresses some of the ways in which anthropology, as a discourse and a discipline, has contributed to the forging as much as of the problematisation of the concept of gender, not only within the feminist, queer and LGBTQI camps, but also among Catholic fundamentalists. It argues that, despite some recent genealogical critiques of the concept of gender and its origins in mid-20th century bio-medical governance, insufficient attention has been paid to the role of the so-called ‘savage slot’ - as Rolph Trouillot defined the domain of knowledge carved out for anthropology, in a wider scheme of thought that has its origins at the same time as ‘the West’ became a reality. A more thorough genealogy of the ways in which anthropological thinking and evidence contributed to the construction, and then the deconstruction, of gender, can provide fruitful tools for a deeper challenge of the apparatus of gender itself.